Case Report: Does extracorporeal membrane oxygenation treatment for acute pulmonary embolism-induced respiratory and cardiac arrest still require thrombolysis? - Qiu, Fangfang; Song, Bingxin; Chen, Lina; Hong, Jiayi (Frontiers in Cardiovascular Medicine, 2025)
Acute massive pulmonary embolism (PE) secondary to cardiac arrest (CA) is associated with extremely high mortality. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) serves as a critical life support modality; however, the safety and necessity of combined thrombolytic therapy remain controversial. This study reports the clinical outcomes of two CA patients with acute PE treated with VA-ECMO: Case 1 underwent ECMO support without thrombolysis, receiving only heparin anticoagulation. Dynamic imaging evaluation demonstrated gradual thrombus resolution, leading to successful weaning from ECMO and subsequent recovery. Case 2 received immediate thrombolysis with alteplase 50 mg after ECMO cannulation but succumbed to severe bleeding complications—including cannulation site hemorrhage, disseminated intravascular coagulation (DIC), and hemorrhagic shock—within 24 h. For ECMO-treated PE patients with CA, clinical decisions should be based on etiological assessment, bleeding risk, and multimodal evaluations (e.g., imaging, coagulation function), prioritizing individualized reperfusion strategies (such as catheter-directed thrombectomy or surgical embolectomy) to improve prognosis. Although both cases described herein received VA-ECMO as salvage therapy, their divergent thrombolytic strategies resulted in contrasting clinical outcomes, prompting critical clinical reflections on risk-benefit balancing in this high-risk population.